Gut Microbiota, Host Organism, and Diet Trialogue in Diabetes and Obesity - Lazar, Veronica; Ditu, Lia-Mara; Pircalabioru, Gratiela G.; Picu, Ariana; Petcu, Laura; Cucu, Natalia; Chifiriuc, Mariana Carmen (Frontiers in Nutrition, 2019)
The gastrointestinal tract with its microbiota is a complex, open and integrated ecosystem with a high environmental exposure. It is widely accepted that the healthy gut microbiota is essential for host homeostasis and immunostasis, harboring an enormous number and variety of microorganisms and genes tailored by hundreds of exogenous and intrinsic host factors. The occurrence of dysbiosis may contribute to host vulnerability and progression to a large spectrum of infectious and non-communicable diseases, including diabetes and obesity, two metabolic disorders that are showing an endemic trend nowadays. There is an urgent need to develop efficient strategies to prevent and treat metabolic disorders such as diabetes and obesity which areoften associated with serious complications. In this paper, we give an overview on the implications of gut microbiota in diabesity, with a focus on the triangle gut microbiota – diet - host metabolism and on the way to manipulate the gut microbial ecosystem towards achieving novel diagnosis and predictive biomarkers with the final goal of re-establishing the healthy metabolic condition. The current research data regarding the precision/personalized nutrition suggest that dietary interventions, including administration of pre-, pro-, and synbiotics, as well as antibiotic treatment should be individually tailored to prevent chronic diseases based on the genetic background, food and beverage consumption, nutrient intake, microbiome, metabolome and other omic profiles.